SOSIALISASI MODEL MENGAJAR INTERAKSIONAL BAGI GURU MTS BABUSSALAM TANJUNG PURA - Satria Wiguna; Nurmisdaramayani Nurmisdaramayani; Ima Sari Ramadhani; Riski Riski (Politeknik Negeri Sriwijaya, 2018)
This socialization aims to find out how the implementation of the interactional teaching model for teachers at MTS Babussalam Tanjung Pura and to find out how students perceive the interactional teaching model for teachers at MTS Babussalam Tanjung Pura and find out how the influence of the teacher interactional teaching model on student perceptions at MTS Babussalam Tanjung Pura. The method of implementation is the preliminary stage, the preparation stage, the implementation stage and the evaluation stage. Results and discussion that the socialization of the interactional teaching model between teachers and students at MTS Babussalam Tanjung Pura is an associative interaction model, where this interaction leads to forms of association such as cooperation, accommodation, and also assimilation. The interaction between teachers and students is always carried out both inside and outside the classroom, both in teaching and learning activities and outside teaching and learning activities. At MTS Babussalam Tanjung Pura, the interaction between teachers and students is always pursued as well as possible, considering whether or not the relationship or interaction between the teacher and students is one of the factors that can affect the level of interest and motivation to learn owned by students. The better the interaction between the teacher and the students, the better the interest and learning motivation of the students will be.